2017
DOI: 10.3389/fphar.2017.00276
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces sp. MUM212 as a Source of Antioxidants with Radical Scavenging and Metal Chelating Properties

Abstract: Reactive oxygen species and other radicals potentially cause oxidative damage to proteins, lipids, and DNA which may ultimately lead to various complications including mutations, carcinogenesis, neurodegeneration, cardiovascular disease, aging, and inflammatory disease. Recent reports demonstrate that Streptomyces bacteria produce metabolites with potent antioxidant activity that may be developed into therapeutic drugs to combat oxidative stress. This study shows that Streptomyces sp. MUM212 which was isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 106 publications
(133 reference statements)
7
91
0
Order By: Relevance
“…S-2, aside from antibiotic activity, might display antitumor, anti-inflammatory, or antioxidant activities, or function as insecticides. Such activities have been previously reported in the Streptomyces genus [2,10,[70][71][72]. Considering the biosynthetic potential of the S-2 strain, future research focusing on investigation of these activities is ensured.…”
Section: Discussionsupporting
confidence: 58%
“…S-2, aside from antibiotic activity, might display antitumor, anti-inflammatory, or antioxidant activities, or function as insecticides. Such activities have been previously reported in the Streptomyces genus [2,10,[70][71][72]. Considering the biosynthetic potential of the S-2 strain, future research focusing on investigation of these activities is ensured.…”
Section: Discussionsupporting
confidence: 58%
“…It has been suggested that understudied ecosystem hold Streptomyces species which can meet the growing demand of drug discovery and development industry [77] . Researchers who made an effort to study Streptomyces from less explored ecosystems such as mangrove forest were able to discover novel Streptomyces species and Streptomyces strains showing potent antioxidant activities [40,42,66,68,78,79] . dards for potential match.…”
Section: Discussionmentioning
confidence: 99%
“…The total phenolic content (TPC) of the methanolic extract of MUSC 11 were determined following the method of Tan et al [66] . A series of concentrations of the extract at 10 µL each were prepared and added into 96 well.…”
Section: Assessing the Total Phenolic Content Of Extractmentioning
confidence: 99%
See 2 more Smart Citations